Coulomb blockade devices of Co dot arrays on tungsten-nanowire templates fabricated by using only a thin film technique - Lee, YH; Kim, DH; Shin, KS; Choi, CH; Jang, YT; Ju, BK (AMER INST PHYSICS, 2003)
A simple fabrication of gate-controlled nanodevices made of the Co nanodots on tungsten (W)-nanowire templates by using conventional photolithography and a thin film technique is reported. The combined multiple grain nanobridge allows the observation of the Coulomb gap up to a temperature as high as 200 K and shows nonlinear current-voltage characteristics up to 250 K. The combination of Co dots with straight W-nanowire templates opens possibilities of reproducible blockade devices. (C) 2003 American Institute of Physics.
Keywords: SINGLE-ELECTRON; SYSTEM; MEMORY